Improving a technique for the estimation and adjustment of counterbalance of sucker-rod pumping units’ drives - Kharun, Victor; Dzhus, Andriy; Gladj, Ivan; Raiter, Petro; Yatsiv, Taras; Hedzyk, Nazarii; Hryhoruk, Oleksandr; Kasatkin, Serhii (Eastern-European Journal of Enterprise Technologies, 2018)
In order to reduce the impact of uneven load on the operation of drives at downhole sucker rod pumping units, it has been proposed, based on the results of this study, to apply an improved technique for estimating and adjusting their counterbalancing. The technique implies determining the required position of crank counterweights based on dependences of change in the active power and the rotation speed of the motor shaft. The experimental research aimed to derive the aforementioned dependences was carried out by using a portable information-measuring complex. Its operation is based on the technology of virtual instruments, methods of digital signal processing, and graphical programming of algorithms for applied software. According to the proposed technique, the optimal position of crank counterweights is determined based on the condition for the equality of maxima of the cumulative torque at the output shaft of the reduction gear. In this case, the diagram of change in the momentum of forces of useful resistance is the difference between the combined torque at the output shaft of the reduction gear, obtained as a result of this research, and a momentum from the crank and counterweights. A possibility to implement the improved technique for adjusting the equilibration of drives was confirmed, with a sufficient accuracy, by results from the repeated wattmeter measurement, performed upon repositioning the crank loads in accordance with the devised recommendations. It has been substantiated that a sufficient accuracy of parameters controlled in order to implement the technique could be achieved under condition that the crank turning angle between measurement points ranges from 5° to 1°. Introduction of the technique would make it possible to minimize the time required for the implementation of the balancing process and to reduce the impact of uneven load on the drive’s operation